Thumb-tip force orediction based on hill’s muscle model using electromyogram and ultrasound signal - Sidek, Shahrul Na'im; Roslan, Muhammad Rozaidi; Sidek, Sabrilhakim; Mohd Khalid, Mohd Shukry (Atlantis Press, 2018)
The use of prostheses is necessary to restore lost limbs to a level of functionality to enable activity of daily living. Many prostheses are now using myoelectric based control techniques to operate. However, to develop a model based controller for the system remains a challenge as accurate model is necessary. This study investigates the use of electromyogram and ultrasound signal to predict thumb tip force based on Hill’s Muscle model. The results obtained has shown a significant improvement in the prediction of thumb tip force as much as 31.45% of average RMSE over the benchmark model that leverages on biomechanics model and active marker to characterize the muscle